Mengoptimalkan Nilai Perusahaan: Mengungkap Peran Moderator Kualitas Audit dalam Hubungan Leverage, Profitabilitas, dan Ukuran Perusahaan - Maukonda, Rana; Assih, Prihat; Subiyantoro, Edi (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
This research delves into assessing the influence of Leverage, as indicated by the Debt to Asset Ratio (DAR), Profitability, measured by Earnings Per Share (EPS), and Company Size on Firm Value in the context of Processed Foods firms listed on the Indonesia Stock Exchange between 2020 and 2022. Additionally, it introduces Audit Quality, gauged by Industry Specialization Auditor, as a moderating variable in this analysis. The study applied a purposive sampling approach, selecting a sample of 19 Processed Foods companies. The quantitative data were collected from annual financial reports available on the Indonesia Stock Exchange website and subsequently subjected to analysis employing Multiple Linear Regression and Moderated Regression Analysis (MRA) using SPSS version 27. The findings of the study reveal that Leverage and Profitability significantly and positively impact Firm Value. However, Company Size exhibits a significant negative effect. Notably, Audit Quality does not appear to moderate the relationships between Leverage and Profitability with Firm Value. In contrast, it does moderate the influence of Company Size on Firm Value. These outcomes provide valuable insights into the dynamics at play within the Processed Foods industry, offering potential guidance for decision-makers seeking to enhance company performance and overall value.